Russian composers abroad : how they left, stayed, returned - Dubinet͡s, Elena Aleksandrovna, 1969- (Russian music studies (Bloomington, Ind.), 2021)
As a Russian émigré herself, Dubinets soberly scrutinizes how, given the multitude of influences inevitably affecting these composers' creative expressions, critics and listeners are wrong to identify them as simply ""Russian.""